2008
DOI: 10.1007/s00284-008-9203-z
|View full text |Cite
|
Sign up to set email alerts
|

Growth Kinetics and Toxicity of Enterobacter cloacae Grown on Linear Alkylbenzene Sulfonate as Sole Carbon Source

Abstract: A successful attempt was made to isolate linear alkylbenzene sulfonate (LAS)-degrading bacteria from soil irrigated with wastewater. The isolated bacteria were able to use LAS as sole carbon and energy source. Maximum growth rates on LAS reached only 0.27 h(-1). 16S-rRNA sequencing and fatty-acid analysis placed the bacteria in the genus Enterobacter cloacae. The growth curves of E. cloacae both in the presence of and the absence of LAS were monitored using measurements of optical density at 600 nm in two diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…It was identified as previously described (Khleifat et al 2008) by 16S rDNA and fatty acid analysis. To guarantee the use of 2-CBA, 3-CBA, 4-CBA, and 3,4-CBA as carbon and energy sources by this bacterium, in preliminary experiment we implied a minimal medium that had these organic compounds as the only carbon sources.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was identified as previously described (Khleifat et al 2008) by 16S rDNA and fatty acid analysis. To guarantee the use of 2-CBA, 3-CBA, 4-CBA, and 3,4-CBA as carbon and energy sources by this bacterium, in preliminary experiment we implied a minimal medium that had these organic compounds as the only carbon sources.…”
Section: Resultsmentioning
confidence: 99%
“…The bacterium used in these experiments, Enterobacter cloacae, was originally isolated from soil irrigated with wastewater on the basis of its ability to grow with linear alkylbenzene sulfonate (LAS) as the sole source for carbon and energy (Khleifat et al 2008). It was identified by 16S rDNA and fatty acid analysis.…”
Section: Materials and Methods Bacterial Strainsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, cells that was adapted to copper had no such a response (Yoneyama and Nakae, 1996;Teitzel et al, 2006). It was reported that, microorganisms are able to adjust to the existence of toxic substances by using a succession of adaptation strategies such as alteration in lipid composition of cell membranes to recompense for these substances induced surge in membrane fluidity (Khleifat, 2007;Khleifat et al, 2008). Bacterial resistance to copper metal has demonstrated an important contribution to the competitive endurance of some pseudomonads in such environment (Yang et al, 1993).…”
Section: Discussionmentioning
confidence: 99%